Openness to Using an External Penile Prosthesis for Maintaining Sexual Intimacy by Individuals with Erectile Dysfunction: A Cross-Sectional Study - Fong Fu, BSc; Cassian J. Duthie; Erik Wibowo, PhD; Richard J. Wassersug, PhD; Lauren M. Walker, PhD, RPsych (Sexual Medicine, 2022)
Introduction: Erectile dysfunction (ED) can lead to reduced sexual intimacy in men. The external penile prosthesis (EPP) is a device to help them participate in penetrative sex. Aim: We investigate factors that may affect the willingness of individuals with ED to try an EPP and explore how the EPP could be presented most effectively to such patients to enhance their willingness to try an EPP. Methods: Recruitment for this cross-sectional study occurred in-person and online. 147 participants (60.0 ± 14.3 years old; all experiencing self-reported ED) completed a survey containing both validated measures and questions specific to this study. The survey was open to English-speakers over the age of 18 who self-reported experiencing ED. Main Outcome Measure: The primary outcome was participants’ willingness to try an EPP based on their level of knowledge about using the EPP. Secondary outcomes included the influence of the sexual function, sexual distress, ED history, age, relationship duration, sexual flexibility on willingness to try an EPP. We also collected feedback from participants’ on how and where they would like to be introduced to the EPP option. Results: Most participants indicated a preference for being introduced to the EPP after trying some ED treatments (51.0%). Participants did not have strong preference regarding the setting where they were informed about the EPP. The majority however preferred having a sexual health therapist/counsellor (28.6%) or physician (25.9%) as the person introducing the EPP to them. Participants’ willingness to try the EPP increased with more information about the EPP presented to them (P < .001). Personalization of the EPP to match one's own penis was preferred by 38.7% of participants. Referring to this aid as an ‘external penile prosthesis’ was significantly more preferred over alternative labels, such as a “belted prosthetic phallus” or “strap-on dildo” (Ps < .001 for both). Multiple regression analyses showed that only sexual script flexibility was associated with the initial willingness to try an EPP (P < .01). Clinical Implications: Clinicians should consider presenting the EPP to men with ED, who desire maintaining penetrative sexual intercourse with their partners. Strength and Limitations: This is the first study to explore factors influencing the willingness to try an EPP. Further research is needed to establish the efficacy of EPPs for maintaining sexual activity and satisfaction in the real-life setting. Conclusion: This study informs clinicians about effective ways to introduce the EPP to patients with ED who wish to maintain insertive/receptive sex.Fu F, Duthie CJ, Wibowo E, et al. Openness to Using an External Penile Prosthesis for Maintaining Sexual Intimacy by Individuals with Erectile Dysfunction: A Cross-Sectional Study. Sex Med 2022;10:100559.